2015 Annual Report to CGIAR Consortium: CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Annual technical report for the CGIAR Consortium describing progress to date, significant achievements and successes In 2015, flagship products and tools, and publications.